Ocean Salinity, Early-Life Health, and Adaptation - Amanda Guimbeau; Xinde James Ji; Zi Long; Nidhiya Menon (Institute of Labor Economics (IZA), 2023)
We study the effects of in utero exposure to climate change induced high ocean salinity levels on children's anthropometric outcomes. Leveraging six geo-referenced waves of the Bangladesh Demographic and Health Surveys merged with gridded data on ocean salinity, ocean chemistry and weather indicators (temperature, rainfall and humidity) from 1993 to 2018, we find that a one standard deviation increase in in utero salinity exposure leads to a 0.11 standard deviation decline in height-for-age. Effects on weight-for-height and weight-for-age for a similar magnitude increase in salinity are 0.13 and 0.15 standard deviations, respectively. Analyses of parental investments and health-seeking behaviors demonstrate that compensating actions along these dimensions to attenuate the detrimental effects of salinity are few and restricted to poorer households. Using satellite-sourced datasets on agriculture and land-use, we find that increasing salinity constrains farmers' land use choices, leading to lower agricultural profitability. In particular, the effects of salinity on child health originate in areas with lower agricultural intensity caused by the progressive salinization of productive lands. These results highlight highlight the costs of environmental insults on early-life health outcomes in vulnerable populations.
Keywords: Q54; Q15; Q56; I15; O13; J13; 330; ocean salinity; early-life health; climate change; height-for-age; weight-for-height; weight-for-age; children; adaptation; Bangladesh